The implementation of the National Media Commission’s Guidelines for Local Language Broadcasting, a conduit for local language media accountability in Ghana - Aboagye Da-Costa, Caroline; Ganaa, Fausta Kilian; Adade-Yeboah, Asuamah (Advances in Social Sciences Research Journal, 2020)
Broadcasting in the local language in Ghana, especially on radio, has come under stakeholder criticisms over years. The National Media Commission (NMC) Ghana’s independent media regulator introduced the Guidelines for Local Language Broadcasting (GLLB) in 2009 as a counterweight to guide the reputation of local language broadcasting. Ten years down the line, the criticisms continue against a backdrop of NMC’S failure to make its impact felt and not being effective in popularising the GLLB among the local language media fraternity. Using interviews, observations and content analysis of the GLLB, the study enhances the GLLB’S implementation by local language radio stations in Ghana with all the perceived challenges. The study found out that for the GLLB to be effectively implemented, the NMC needs an elevation to the status of an Authority in order to command enormous power to exercise. The tenets of the GLLB also need to be re-visited and revised from a Guideline into a Standard, after consultations with the relevant stakeholders.